'People want newspapers far more than weekly collections of articles': The Sheffield Guardian, the Labour Party and the left-wing press. Issue 3 (December 2015) - Vessey, David
Abstract : Local newspapers such as the Sheffield Guardian provide valuable insight into the development of the Labour Party and the wider left-wing press in early twentieth-century Britain. The Guardian 's ten-year history between 1906 and 1916 reflects how Labour's political identity evolved in Sheffield, progressing through struggles to preserve Labour's independence and commitment to socialist principles against co-operation with rival parties, to a more pragmatic and less idealistic attitude that more adequately recognized the everyday concerns of potential working-class supporters. This tussle eventually centred on the Guardian itself as Attercliffe MP Joseph Pointer sought to transform the paper from its status as a niche publication that had previously acted as a polemical platform for old editor and initial creator, Alfred Barton. Consistent interaction with national figures in the Labour Party, particularly Ramsay MacDonald, also reveals the often problematic relationship between the local movement and national policy. Furthermore, changes to the style, content and management of the Guardian were indicative of the wider state of the left-wing press as Labour hesitated to ameliorate its focus on propaganda by recognizing the continuing commercialization of print media in British society.